Development of a wireless mesh network routing algorithm for oil and gas pipeline networks - Azman, Amierul Syazrul Azril (2021)
In the past decades, wireless sensor networks (WSNs) progressed with more advanced and sophisticated wireless technologies and sensors, predominantly for high-risk applications such as oil and gas pipelines remote monitoring. In the refinery area of oil and gas, a large scale of multi-points of sensing is required due to the wide distribution of pipeline network. WSN accommodates the collection of the gathered sensory data to the sink station with quality of service proportional to the network density. A larger amount of data are generated into the traffic as more number of sensor nodes introduced in the network. Since oil and gas pipeline monitoring application requires continuous data gathering, every sensor node will have to continuously transmit its data to the destination node. Consequently, the network will be experiencing bottleneck and performance degradation state due to the accumulation factor of the packets in the queue. Apart from that, due to different data rate area, the network resources have been utilised by the nodes without fairly manner, where the nodes closer to the destination point consume more resources and energy as compared to the nodes further from the sink point. The purpose of this research is to develop an enhanced routing algorithm suitable for oil and gas pipeline application in the refinery area. The second purpose of this research is to analyse the performance of the developed algorithm. A reactive routing algorithm, known as Odd-Even for Grid (OEG), has been developed for grid multi-hop topology to ensure the network is applicable for an application that requires wide coverage area, such as oil and gas refinery pipeline integrity monitoring. OEG algorithm implements load balancing features to lessen the contention of the packets in the traffic by separating the traffic into odd and even traffic. With the exception of the sink point, a node with even/odd-numbered address will only communicate with the rest of the respective nodes with even/odd-numbered address. By using OEG algorithm, the amount of broadcast packets also can be reduced. In accordance with IEEE 802.11, the tested and observed results in different simulation environment have shown an improved overall network performance in terms of packet delivery ratio (1–60%), throughput (1–19kbps), passive nodes (1-48%), fairness index (0.04-0.19), and energy consumption (0.01-1.48J). The improvement on packet delivery ratio using OEG algorithm has satisfied the benchmark of packet delivery ratio used by the other researchers for industrial applications. Hence, as compared to AODV and OLSR, OEG algorithm can suit better for continuous sensing application such as oil and gas pipeline monitoring. The research has highlighted the incompetency of the deliverable of the fairness index as the lacking point of OEG algorithm.